Take me to the river [videorecording (DVD)] - Shore, Martin; Howard, Terrence; Howard, Terrence; Bell, William, 1939-; Snoop Dogg, 1972-; Staples, Mavis (Shout Factory, 2015)
Documentary celebrating the intergenerational, interracial, and undeniable influence of Memphis, Tennessee on American culture and its music, bringing together award-winning Memphis and Mississippi Delta musicians for a one-of-a-kind musical project and following them through the creative process of recording a historic new album. Features Terrence Howard, William Bell, Snoop Dogg, Mavis Staples, Otis Clay, Yo Gotti, Bobby Rush, Frayser Boy, North Mississippi All-Stars, and others.